Incidencia de los defectos comunicacionales de los espacios radiales de la emisoras radio Santiago y radio pública de Guayaquil en la prevención del crimen racial y por género en la cooperativa Nigeria - Guerrero Pérez, Melissa (2014)
This project is the result of research conducted at the communicative effects of radio programs in preventing racial and gender discrimination. Aims to analyze the content and communicative effects of such spaces. Communication is not limited to the transmission of meaning between people through oral or written language but rather, it is a way to convey a message that causes a positive multiplier effect and its receptors.....